EFFECT OF CHINESE MEDICAL HERBS-HUIRU YIZENG YIHAO ON HYPERPROLACTINEMIA AND HYPERPLASIA OF MAMMARY GLAND IN MICE - Wang, Xiong; Chen, Yong-gang; Ma, Li; Li, Zhi-hui; Li, Ju-yi; Liu, Xin-guo; Zou, Ji-li; Wu, Jin-hu (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The study investigated the pharmacodynamism and mechanism of Chinese medicinal formula-Huiru Yizeng Yihao (NO.1 HRYZ) on the model rats of hyperpro-lactinemia and the model rats of hyperplasia of mammary gland (HMG), and studied the internal connection between hyperprolactinemia and HMG.. The hyperprolactinemia rat models were established by injecting metoclopramide dihydrochloride in the back of rats. The model rat of HMG was prepared by injecting estradiol in the thigh muscle of the rats and progesterone consecutively, while the tails of rats were clipped with tongs. Rats were treated with either NO.1 HRYZ or positive control drugs for four weeks. The concentrations of sex hormone in rat serum were examined using ELISA kits, and the morphology of mammary gland tissue in all group rats was observed with microscope. NO.1 HRYZ significantly decreased prolactin (PRL) and increased estradiol (E2), progesterone (P), follicle stimulating hormone (FSH), luteinizing hormone (LH) concentrations of hyperprolactinemia rats. It decreased E2, PRL, FSH, gonadotropin-releasing hormone (GnRH), 5-hydroxytryptamine (5-HT) and increased P concentrations of HMG rat. It also eliminated hyperplasia of lobules and gland alveolus compared with the model group. Treatment with NO.1 HRYZ could significantly regulate the sex hormone disorder of hyperprolactinemia and HMG rat models, and could eliminate the formation of HMG. Hyperprolactinemia was closely correlated with HMG, and hyperprolactinemia promoted the formation of HMG.